New data on the distribution and host plants of subfamily Buprestinae (Coleoptera: Buprestidae) in Bulgaria - Vladimir Sakalian; Enrico Migliaccio; Victor Gashtarov; Danail Doychev; Georgi Georgiev (Silva Balcanica, 2021)
Data about the distribution and host plants of 47 species group taxa from subfamily Buprestinae are presented. In this study, three localities of Anthaxia (Anthaxia) suzannae were reported for the first time in Bulgaria. In addition, Paliurus spina-christi was established as a new host plant for Chrysobothris leonhardi.